2019
DOI: 10.1111/1753-0407.12995
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and semen quality in adult population

Abstract: Background Male obesity is suggested to impact negatively on male fertility and semen quality in numerous studies. However, previous literatures regarding health effects of the metabolic syndrome (MetS) on semen quality are rare and inconsistent. The aim of this study is to investigate the relationship between MetS and sperm parameters in a Taiwanese reproductive‐age male population. Methods A total of 8395 men who attended a private medical screening program in Taiwan from 2010 to 2016 were included in this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Overall, six studies [55,[64][65][66]68,69] found a lower sperm motility (regardless of the type of motility considered) in men with MetS than in those without, while three [65,66,69] reported a lower "sperm progressive motility" in MetS men. Of note, one study [66] found a lower sperm progressive motility in infertile men with MetS than in fertile men without, but no difference comparing fertile men with and without MetS (Tables 3 and 5).…”
Section:  Sperm Motilitymentioning
confidence: 94%
See 3 more Smart Citations
“…Overall, six studies [55,[64][65][66]68,69] found a lower sperm motility (regardless of the type of motility considered) in men with MetS than in those without, while three [65,66,69] reported a lower "sperm progressive motility" in MetS men. Of note, one study [66] found a lower sperm progressive motility in infertile men with MetS than in fertile men without, but no difference comparing fertile men with and without MetS (Tables 3 and 5).…”
Section:  Sperm Motilitymentioning
confidence: 94%
“…The rest of the studies (Tables 3 and 5) Tables 3 and 5). Four studies [47,56,58,68] found a lower normal morphology in men with MetS than in those without. One study [66] found a lower normal sperm morphology in infertile men with MetS than in fertile men without MetS, but no difference in sperm morphology comparing fertile men with and without MetS (Tables 3 and 5).…”
Section:  Sperm Motilitymentioning
confidence: 98%
See 2 more Smart Citations
“…The search strategy identified 5,272 records: 702 from PubMed, 4,554 from Embase, and 16 from other sources (Figure 1). After eliminating duplicated and irrelevant records, 10 recodes (11 studies) were included in the meta-analysis, with a total of 1,731 MetS cases and 11,740 controls ( Table 1) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The research by Ehala-Aleksejev and Punab (19) was based on two cohorts (fertile men and male partners of infertile couples), and thus it was divided into two individual studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%